The impact of the Zimbabwean Space Agency’s programme for the mapping of mineral reserves on foreign direct investment in Zimbabwe - Abe, Oyeniyi (University of Pretoria, 2020)
Mini Dissertation (LLM)--University of Pretoria, 2019.